HIGHLY REFRACTORY CRUCIBLES OF STABILIZED ZIRCONIA FOR INDUCTION MELTING OF THE PLATINUM GROUP METALS, FABRICATED BY VIBROCASTING - V. V. Primachenko; V. V. Martynenko; I. G. Szulik; I. A. Kushchenko (Литьë и металлургия)
As the result of the studies at PJSC « UKRNIIO them. A.S.Berezhnogo» the technology and commercial production of crucibles from stabilized zirconia for the smelting of platinum group metals are develop